2021
DOI: 10.1038/s41598-021-00100-4
|View full text |Cite
|
Sign up to set email alerts
|

Genic microsatellite marker characterization and development in little millet (Panicum sumatrense) using transcriptome sequencing

Abstract: Little millet is a climate-resilient and high-nutrient value plant. The lack of molecular markers severely limits the adoption of modern genomic approaches in millet breeding studies. Here the transcriptome of three samples were sequenced. A total of 4443 genic-SSR motifs were identified in 30,220 unigene sequences. SSRs were found at a rate of 12.25 percent, with an average of one SSR locus per 10 kb. Among different repeat motifs, tri-nucleotide repeat (66.67) was the most abundant one, followed by di- (27.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…The most plausible explanation for a higher frequency of trinucleotide SSRs than dinucleotide SSRs within transcriptome sequences is the fact that they do not cause frameshift of coding sequences. AG/CT and GA/TC dinucleotide repeats and CGC/GCG and CCG/CGG trinucleotide repeats were the most abundant repeat motifs revealed in this study, which were also common in other monocot crops, such as little millet (Desai et al, 2021), bread wheat (Yang et al, 2016) and radish (Zhai et al, 2014). The abundance of CCG/CGG motifs in finger millet is consistent with previous findings in monocots (rice, maize, and wheat) (Morgante et al, 2002).…”
Section: Ssr and Snp Markerssupporting
confidence: 91%
See 1 more Smart Citation
“…The most plausible explanation for a higher frequency of trinucleotide SSRs than dinucleotide SSRs within transcriptome sequences is the fact that they do not cause frameshift of coding sequences. AG/CT and GA/TC dinucleotide repeats and CGC/GCG and CCG/CGG trinucleotide repeats were the most abundant repeat motifs revealed in this study, which were also common in other monocot crops, such as little millet (Desai et al, 2021), bread wheat (Yang et al, 2016) and radish (Zhai et al, 2014). The abundance of CCG/CGG motifs in finger millet is consistent with previous findings in monocots (rice, maize, and wheat) (Morgante et al, 2002).…”
Section: Ssr and Snp Markerssupporting
confidence: 91%
“…Possible reasons includes lack of sequenced databases for finger millet, short sequence length of some of the unigenes, the presence of non-coding sequences or sequences of untranslated regions, and a high sequence variation that results in an E-value above the cutoff. This is in line with the findings of Desai et al (2021); Zhang et al (2021), and (Kim et al, 2022), who found a large proportion of gene sequences that lacked significant sequence similarity hits in various databases.…”
Section: Annotation Of the Unigenessupporting
confidence: 90%
“…Gene-based SSR markers are a highly valuable resource and could be used for functional diversity analysis, comparative mapping, evolutionary analysis, and molecular plant breeding (Varshney et al, 2005). Gene-based SSR markers were developed in several crop plants like rice (Molla et al, 2015), barley (Zhang et al, 2014), wheat (Kumar et al, 2018;Singh et al, 2018;Mehta et al, 2021), millet (Desai et al, 2021) and many others. For wheat dMTase genes, we also identified 17 SSR motifs and designed primer pairs (Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, molecular markers such as AFLP, RAPD, CAP, miRNA, EST, ISSR, SRAP, DEG, and SNP in proso millet were implied for genotyping the diversity, while EST, RAPD, and AFLP were used to analyze the calcium dynamics in finger millet ( Habiyaremye et al, 2017 ). Fukunago et al (2002b) and Desai et al (2021) studied chloroplast and mitochondrial diversity in foxtail millet and barnyard millet, respectively. Among all molecular markers, SSRs were predominantly utilized in small millets and were also used in comparative genomics to analyze their lineages.…”
Section: Progress Of Crop Improvement In Small Milletsmentioning
confidence: 99%